2019
DOI: 10.1007/s00204-019-02591-7
|View full text |Cite
|
Sign up to set email alerts
|

Towards grouping concepts based on new approach methodologies in chemical hazard assessment: the read-across approach of the EU-ToxRisk project

Abstract: Read-across is one of the most frequently used alternative tools for hazard assessment, in particular for complex endpoints such as repeated dose or developmental and reproductive toxicity. Read-across extrapolates the outcome of a specific toxicological in vivo endpoint from tested (source) compounds to "similar" (target) compound(s). If appropriately applied, a read-across approach can be used instead of de novo animal testing. The read-across approach starts with structural/ physicochemical similarity betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 103 publications
(85 citation statements)
references
References 47 publications
1
84
0
Order By: Relevance
“…Also, the absence of a certain mechanism or effect can be demonstrated, as well as the relatively low potency for a certain testing endpoint. The EU-ToxRisk RAx testing framework demonstrated how NAMs can be integrated into practical RAx procedures (Escher et al 2019 ).
Fig.
…”
Section: Incorporation Of Nams In Read-across Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, the absence of a certain mechanism or effect can be demonstrated, as well as the relatively low potency for a certain testing endpoint. The EU-ToxRisk RAx testing framework demonstrated how NAMs can be integrated into practical RAx procedures (Escher et al 2019 ).
Fig.
…”
Section: Incorporation Of Nams In Read-across Approachesmentioning
confidence: 99%
“…This entails the implementation of NAM-based safety science into regulatory toxicology (Krebs et al 2020b ). The project initially focused on read-across (RAx) (Escher et al 2019 ; Rovida et al 2020a ) and here we outline key outcomes and general learnings on the use of NAMs for RAx. This collection of outputs will facilitate new efforts in next-generation risk assessment (NGRA) (Dent et al 2018 ; Dearfield et al 2017 ; Cote et al 2016 ; Krewski et al 2014 ) and thus advance the field of safety assessment by more mechanistically driven and animal-free approaches (Suppl.…”
Section: Introductionmentioning
confidence: 99%
“…Within the EU-funded consortium EU-ToxRisk, a large integrated European in vitro "flagship" toxicology project exploring new alternative-to-animal approaches to chemical safety evaluation (Daneshian et al 2016;Escher et al 2019;Leist et al 2017), one project addresses alternatives to mammalian teratogenicity testing, which, especially from an animal welfare point of view, represents a major challenge. One alternative approach to mammalian testing is based on the use of early developmental stages of lower vertebrates (fish), which are not regarded protected according to current EU animal welfare legislation (EU 2010;Strähle et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…One of our most important advances was the template for a comprehensive methods description, and a related database for the methods of this study (Krebs et al 2019b ), and this achievement of the CSY has been used subsequently to document methods in read-across (RAx) case studies (Escher et al 2019 ). The regulators reviewing the case studies found the transparent disclosure of all methods very important, and they suggest the RAx studies to be submitted to the OECD as examples for good practice.…”
Section: Discussionmentioning
confidence: 99%